OCCURRENCE OF FUSARIUM SPECIES IN MAIZE GRAINS FOR SILAGE - Krnjaja, Vesna; Lević, Jelena; Stanković, Slavica; Bijelić, Zorica (Plant Breeding and Seed Science, 2011)
Grain samples of two maize hybrids, medium early (ZP434) and late maturity (ZP704), collected during harvest in 2008 were investigated for contamination by fungi. Grains were plated on agar media and grown fungi were identified by morphological macroscopic and microscopic characteristics on potato-dextrose agar (PDA) and synthetic nutrient agar (SNA). Species of the genus Fusarium were the most common in both hybrids, and their presence amounted to 33.89% (ZP434) and 42.00% (ZP704). Other fungi of genera, Acremonium, Alternaria, Aspergillus, Chaetomium, Cladosporium, Nigrospora, Penicillium, Rhizopus and Trichotecium, were isolated from 0 to 41.00%. Four species belonging to the genus Fusarium were identified, of which the species F. verticillioides was the most common with 28.63% in ZP434 and 30.50% in ZP704 hybrids. The presence of F. graminearum, F. proliferatum and F. subglutinans ranged from 3.00% (ZP704) to .00% (ZP434), 0.13% (ZP434) to 7.00% (ZP704) and 0.13% (ZP434) to 7.00% (ZP704), respectively. Generally, the incidence of every particular fungus was higher in the late maize hybrid with a higher moisture content than in the medium-early hybrid with a lower moisture content.